The antecedents of financial wellness among young employees: empirical evidence in Kuala Lumpur / Zahariah Mohd Zain …[et al.] - Mohd Zain, Zahariah; Basir Malan, Irfah Najihah; Mokhtar, Marziah; Mohamad Arshad, Azlin Shafinaz; Abdul Rashid, Arlinah; Mohamad Arshad, Afiza Azura; Mohd Arifin, Azitadoly; Mokhtar, Rosmashitah (Universiti Teknologi MARA, Shah Alam, 2019)
The purpose of this study is to examine the antecedents of financial wellness among young employees in Kuala Lumpur. A survey was carried out to acquire data from 324 young employees using a self-administered on-line questionnaire, utilizing convenience sampling. Results showed that financial stress, work environment, locus of control and financial behavior has significant relationship with financial wellness. It was found that financial stress, work environment, locus of control and financial behavior has significant effect on respondents’ financial wellness. Based on the results, financial wellness can be enhanced through the decreased of the employees’ financial stress and increasing of their work environment, locus of control and financial behavior.